The GEOVIDE cruise in May–June 2014 reveals an intense Meridional Overturning Circulation over a cold and fresh subpolar North Atlantic - P. Zunino; P. Lherminier; H. Mercier; N. Daniault; M. I. García-Ibáñez; F. F. Pérez (Biogeosciences, 2017)
The GEOVIDE cruise was carried out in the subpolar North Atlantic (SPNA) along the OVIDE section and across the Labrador Sea in May–June 2014. It was planned to clarify the distribution of the trace elements and their isotopes in the SPNA as part of the GEOTRACES international program. This paper focuses on the state of the circulation and distribution of thermohaline properties during the cruise. In terms of circulation, the comparison with the 2002–2012 mean state shows a more intense Irminger Current and also a weaker North Atlantic Current, with a transfer of volume transport from its northern to its central branch. However, those anomalies are compatible with the variability already observed along the OVIDE section in the 2000s. In terms of properties, the surface waters of the eastern SPNA were much colder and fresher than the averages over 2002–2012. In spite of negative temperature anomalies in the surface waters, the heat transport across the OVIDE section estimated at 0.56 ± 0.06 PW was the largest measured since 2002. This relatively large value is related to the relatively strong Meridional Overturning Circulation measured across the OVIDE section during GEOVIDE (18.7 ± 3.0 Sv). By analyzing the air–sea heat and freshwater fluxes over the eastern SPNA in relation to the heat and freshwater content changes observed during 2013 and 2014, we concluded that on a short timescale these changes were mainly driven by air–sea heat and freshwater fluxes rather than by ocean circulation.